Facile synthesis of free-standing Fe2O3/carbon nanotube composite films as high-performance anodes for lithium-ion batteries. Issue 129 (14th December 2015) - Yang, Deming; Xu, Shanshan; Dong, Shuilang; Liu, Jiachen; Guo, Anran; Yan, Xiao; Hou, Feng
Abstract : Continuous Fe nanoparticles (NPs)/carbon nanotube (CNTs) composite films have been fabricated with the CVD gas flow reaction using ferrocene as a catalyst and ethanol as a carbon precursor. Abstract : Continuous Fe nanoparticles (NPs)/carbon nanotube (CNTs) composite films have been fabricated with the CVD gas flow reaction using ferrocene as a catalyst and ethanol as a carbon precursor. The as-spun Fe NPs/CNTs films are converted to Fe2 O3 NPs/CNTs films by an annealing process in air at a temperature of 500 °C. The as-prepared Fe2 O3 NPs/CNTs films are still highly flexible. Scanning electron microscopy (SEM) and transmission electron microscopy observations reveal the Fe2 O3 NPs are homogeneously bonded with the CNT network. In addition, the flexible and conductive 3D CNTs networks endow the as-synthesized composite with increased electrical conductivity and mechanical stability. As a result, the as-synthesized flexible and transferrable composite films deliver an initial reversible capacity of 985.8 mA h g −1 at a current density of 30 mA g −1, and maintain a high reversible capacity of 392.4 mA h g −1 even at a current density up to 3 A g −1 . Meanwhile, Fe2 O3 NPs/CNTs films exhibit an excellent cycling performance with a reversible capacity of 375.5 mA h g −1 after 800 cycles at a current density of 3 A g −1 .